Wooden sacral architecture in Greater Poland. An interdisciplinary case study of the church in Domachowo - Różański, Artur; Jurek, Tomasz; Marciniak, Piotr; Łobodzińska, Patrycja; Schaaf, Ulrich (Archaeologia Historica Polona, 2020)
Sacred wooden architecture in Poland is a huge and still unrecognised research problem. It covers a number of issues of interdisciplinary character: from the properties of building materials and carpentry techniques, through construction and architectural-spatial solutions, to cultural and natural conditions. Hence, the best way to study this problem is interdisciplinary research. The necessity of cooperation of representatives of various scientific disciplines became the basis for creating a team to study the wooden church of St Michael the Archangel in Domachowo, so far dated to 1568. As researchers representing various disciplines (including archaeology, history, art history, history of architecture, architecture, architectural conservation), we cite sources and research that allow us to formulate a thesis that the past of the Domachowo church dates back to the 14th century. Moreover, we present the research and methodological problems inscribed in the aforementioned church building, understood as a whole. Such a multifaceted approach allows us to redefine the current knowledge about the church in Domachowo.